Ecranization of The Yakou Kanransha Novel by Minato Kanae - Alfahira, A. Fany; Anwar, Fithyani (HUMANIKA, 2024)
The public's high appreciation of popular novels has encouraged the film and television industries to adapt literary works into an audiovisual format. One of the novels adapted into a drama series is Yakou Kanransha by Minato Kanae. The ecranization of the novel resulted in changes in the plot, characters, and setting and also impacted the audience’s satisfaction with the drama series. This study uses a descriptive qualitative, and structural approach to analyze the ecranization process of the Yakou Kanransha novel into a drama series to identify the changes between the novel version and the drama series adaptation. Data were obtained from reading the novel and watching the drama series, then analyzing the plot, character, and setting differences. The results showed that the ecranization process resulted in changes in the story structure, including reduction, addition, and varied changes in the aspects of plot, character, and setting. In the plot aspect, there are 8 reductions, 39 additions, and 15 varied changes. Meanwhile, there are 3 reductions, 9 additions, and 8 varied changes in the character aspect. As for the background aspect, there is 1 reduction, 8 additions, and 6 varied changes. The impact of the ecranization process gives different interpretations to the audiences of the two works. Nevertheless, the overall ecranization process has a positive impact, as seen from the positive responses of the audience to the adaptation.